2014
DOI: 10.1002/ejic.201400016
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Agent Degradation with Polyoxoniobates

Abstract: Polyoxoniobates are exceptional amongst polyoxometalates in that they can potentially perform base catalysis in water, a process in which a proton is bonded to an oxo ligand, and a hydroxyl is released. Catalytic decomposition of chemical warfare agents such as organofluorophosphates that were used recently in the infamous civilian attacks in Syria is one opportunity to employ this process. Upon evaluation of the polyoxoniobate Lindqvist ion, [Nb 6 O 19 ] 8-, fast neutralization kinetics was discovered for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 40 publications
(28 reference statements)
2
66
0
Order By: Relevance
“…Control measurements without catalyst revealed negligible hydrolysis (less than 3% after 60 min;F igure S13). We have also investigated Zr-based clusters and Zr(OH) 4 as catalysts for the hydrolysis of DMNP over 60 min, they gave 20 %a nd negligible conversion, respectively. [13] We conclude,t herefore,t hat the reaction indeed is catalyzed by as olid, and not by asoluble molecule or metal ion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Control measurements without catalyst revealed negligible hydrolysis (less than 3% after 60 min;F igure S13). We have also investigated Zr-based clusters and Zr(OH) 4 as catalysts for the hydrolysis of DMNP over 60 min, they gave 20 %a nd negligible conversion, respectively. [13] We conclude,t herefore,t hat the reaction indeed is catalyzed by as olid, and not by asoluble molecule or metal ion.…”
Section: Methodsmentioning
confidence: 99%
“…[4] Although phosphate esters can be hydrolyzed directly with water, [4a] the reaction rate is too slow for realworld applications which often require an early immediate response.T hus,w eh ave been investigating catalysts for the rapid detoxification of nerve-agent stimulants by both hydrolysis and methanolysis.H omogeneous dimers and tetramers of aluminum-porphyrin-based catalysts showed enhanced hydrolysis by catalytic acid activation of the phosphate.Ahalf-life (t 1/2 )o f1 0h for the methanolysis reaction was attributed to the favorable positioning of pairs of acidic Al III sites. [5] Porous organic polymers (POPs) containing Al-porphyrins or La-catecholates moieties demonstrated an early seven-fold greater methanolysis rates (t 1/2 = 90 min).…”
mentioning
confidence: 99%
“…Hexaniobate ions are known to form ion-pairs with Cs + (aq) , Rb + (aq) and K + (aq) ions (Antonio et al, 2009;Kinnan et al, 2014). It was recently reported that ion-pairs formation decreases along the series Cs > Rb > K > Na > Li and that Nb 6 O 19 8-(aq) ion does not interact with Li + (aq) ions (Antonio et al, 2009;Kinnan et al, 2014;Fullmer et al, 2014). The sodium case has not been treated in the literature and, consequently, we tried different models to fit our solubility measurements.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…As such, they are attractive candidates for OP decontamination, as noted in two recent studies that have used polymeric niobates 20, 21 . The experimental work with Cs 8 [Nb 6 O 19 ] 21 has also been recently augmented by a theoretical study of the reaction mechanism at the gas-surface interface involving Sarin 25 . While previous experiments appear to support the prediction that the mechanism follows general base hydrolysis, many atomistic details of the reaction, including the nature of the active sites, their dynamic changes during reaction, and the characterization of intermediates or products, have yet to be experimentally investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to other [Nb 6 O 19 ] alkali salts, the Cs-based analogue exhibits a higher nerve- agent- simulant decontamination rate for reaction on the POM surface than for the analogous reaction in solution 21 , which makes it a promising material for decomposition of OP compounds at the solid-gas interface and greatly broadens the applicability of these materials.…”
Section: Introductionmentioning
confidence: 99%